(untitled) (ELang | An English Language Education Journal, 2025)
This study, titled “An Analysis of Students’ Anxiety in Speaking English among Second-Semester Students”, investigates the dominant factors contributing to students’ speaking anxiety, focusing on internal and external influences. Using a descriptive qualitative approach, data were collected from 22 English Education students at Bale Bandung University through questionnaires and interviews. The PSCAS questionnaire (Yaikhong & Usaha, 2012) revealed that external factors, particularly lack of preparation (loading score: 0.90), were the main sources of anxiety, while lack of motivation (loading score: 0.53) had the least impact. Interview results showed that students commonly overcame anxiety through preparation, confidence-building, and relaxation techniques, while less frequent strategies included listening to music, expanding vocabulary, and practicing pronunciation.